Uncovering the monogenean species diversity of cyprinoid fish in Iraq using an integrative approach - Benovics, M; Rahmouni, C; Řehulková, E; Nejat, F; Šimková, A (Parasitology, 2024)
The freshwaters of Iraq harbour a high diversity of endemic and phylogenetically unique species. One of the most diversified fish groups in this region is cyprinoids, and although their distribution is relatively well known, their monogenean parasites have only rarely been investigated. Herein, we applied an integrative approach, combining morphology with molecular data, to assess the diversity and phylogeny of cyprinoid-associated monogenean parasites. A total of 33 monogenean species were collected and identified from 13 endemic cyprinoid species. The highest species diversity was recorded for Dactylogyrus (Dactylogyridae, 16 species) and Gyrodactylus (Gyrodactylidae, 12 species). Four species of Dactylogyrus and 12 species of Gyrodactylus were identified as new to science and described. Two other genera, Dogielius (Dactylogyridae) and Paradiplozoon (Diplozoidae), were represented only by 4 and 1 species, respectively. Phylogenetic analyses of the Dactylogyrus and Gyrodactylus species revealed that the local congeners do not form a monophyletic group and are phylogenetically closely related to species from other regions (i.e. Europe, North Africa and Eastern Asia). These findings support the assumption that the Middle East served as an important historical crossroads for the interchange of fauna between these 3 geographic regions.
Keywords: Cyprinoidei; Dactylogyrus; Phylogeny; Střední východ; ryby; Trematoda; severní Afrika; Middle East; Irák; zvířata; Fishes; Africa, Northern; fylogeneze; Iraq; phylogeny; Animals; Dogielius; Gyrodactylus; Paradiplozoon; species diversity